الخطر الجزائي للصفقة العمومية في إطار التنمية المستدامة - فايزة, قاصدي (جامعة الوادي.University eloued, 2021)
لقد استخدمت الصفقات العمومية كوسيلة من أجل النهوض بحماية البيئة ومحاربة الفقر والتهميش وذلك عن طريق إدراج مقتضيات التنمية املستدامة في عمليات الشراء العمومي، وذلك حسب املرسوم الرئاس ي رقم 15-247( ج.ر: رقم 50 املؤرخة في 20 سبتمبر 2015 )ضمن الفصل الرابع بعنوان "تنفيذ الصفقات العمومية وأحكام تعاقدية"، القسم األول منه "البيانات اإللزامية" في مادته 95 ..." : البنود املتعلقة بحماية البيئة والتنمية املستدامة". إمكانية املساس بمبادئ الصفقات العمومية من خالل أهداف التنمية املستدامة أثناء Public transactions have been used as a means of promoting environmental protection and combating poverty and marginalization by incorporating sustainable development requirements into public acquisition processes; in accordance with Presidential Decree No . 15-247 (O J No: 50 of 20 September 2015) within Chapter IV entitled: "implementing Public transactions and contractual provisions", the first section concerns "mandatory data" in article 95:". Environmental protection and sustainable development". However, the possibility of compromising the principles of public transactions through the sustainable development objectives during the process of concluding a public transaction is the corpus delicti of the nepotism offence, and it carries the meaning of the penal risk and therefore we must be careful after knowing it
المجلد 12 العدد 02
Keywords: الصفقات العمومية؛ الخطر الجزائي؛ التنمية املستدامة؛ املبادئ العامة; Public transactions; penal risk; sustainable development; general principles; favoritism.